2017
DOI: 10.1103/physreva.95.062503
|View full text |Cite
|
Sign up to set email alerts
|

Resonance-to-intercombination-line ratios of neonlike ions in the relativistic regime

Abstract: We report measurements of the intensity ratio of the 1s 2 2s 2 2p 5 1/2 3d 3/2 → 1s 2 2s 2 2p 6 resonance line to the 1s 2 2s 2 2p 5 3/2 3d 5/2 → 1s 2 2s 2 2p 6 intercombination line in neonlike Kr 26+ and Mo 32+. The measurements were performed at the EBIT-I electron beam ion trap facility at the Lawrence Livermore National Laboratory and utilized an x-ray microcalorimeter. The measured ratio for Mo 32+ , is in four times closer agreement with theoretical predictions than earlier measurements of ions with low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The Ne-like 3C, 3D and y3 Mo 32+ lines may be blended with Na-like Mo lines at low electron beam energies, and with F-and O-like Mo lines at higher electron beam energies, hence making the polarization analysis more difficult. For example, unresolved Na-like lines that blend with the Ne-like 3C and 3D lines at a 4 keV electron beam energy were discussed by Panchenko et al [33], who found that this blending might enhance the apparent intensity of the 3C and 3D lines by 4%-5%. Additionally, the 3D line is blended with the Ne-like forbidden electric quadrupole transition, 2p 5 3p 1 D 2 →2p 6 1 S 0 , denoted as y1 in Young et al [40,41] and E21 in Rice et al [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Ne-like 3C, 3D and y3 Mo 32+ lines may be blended with Na-like Mo lines at low electron beam energies, and with F-and O-like Mo lines at higher electron beam energies, hence making the polarization analysis more difficult. For example, unresolved Na-like lines that blend with the Ne-like 3C and 3D lines at a 4 keV electron beam energy were discussed by Panchenko et al [33], who found that this blending might enhance the apparent intensity of the 3C and 3D lines by 4%-5%. Additionally, the 3D line is blended with the Ne-like forbidden electric quadrupole transition, 2p 5 3p 1 D 2 →2p 6 1 S 0 , denoted as y1 in Young et al [40,41] and E21 in Rice et al [38].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the 2p 5 3d 1 P 1 →2p 6 1 S 0 and 2p 5 3d 3 D 1 →2p 6 1 S 0 electric dipole transitions, commonly dubbed 3C and 3D following the notation of Parkinson et al [26], dominate the spectral emission of the Sun and many other stars in the Fe soft x-ray range [26][27][28], and their intensities have been used to diagnose astrophysical sources (see, for example, [29,30]). The LLNL EBIT facility has been used to study the 3C/3D line intensity ratio along the Ne-like isoelectronic sequence for ions between Cr 14+ and Kr 26+ , as well as Mo 32+ [31][32][33]. Before comparing measured results for intensity ratios or cross sections with theory, polarization effects must be taken into account, including polarization dependent crystal reflectivities.…”
Section: Introductionmentioning
confidence: 99%
“…Next to various satellite and balloon missions [45][46][47][48], the XRS spectrometer [49] and its successor ECS [50] are deployed at the EBIT and SuperEBIT of the Lawrence Livermore National Laboratory [12]. Both microcalorimeter arrays have produced outstanding X-ray reference data for astrophysics [1,51,52]. Other applications include high-resolution spectroscopy of xenon [53] and praseodymium [54] for QED tests, spectroscopy on tungsten for fusion research [55] and the investigation of X-ray transitions in thorium-229 for the development of an atomic clock [56].…”
Section: Working Principle Of Resistance Thermometersmentioning
confidence: 99%
“…The variation of the 3C/3D oscillator strengths across the Ne-like isoelectronic sequence with respect to the atomic number Z provides an avenue to investigate various effects that contribute to the experimental-theoretical deviations, such as electron-correlation effects [47][48][49][50][51], population corrections [48,[52][53][54], and polarization [55,56]. Recently, Yang et al [14] demonstrated that there is an apparent change in the 3C/3D line-intensity ratio at approximately Z = 54, attributed to the suppressed collision strength for the upper level of the 3D line due to strong configuration mixing with the upper level of the adjacent 3F {2p 6 -(2p 5 1/2 3s 1/2 ) J=1 , 2.7288 Å [6]} line.…”
Section: Introductionmentioning
confidence: 99%